Effectiveness of an educational asthma management program (CuidAR): the protocol for a cluster-randomized trial in the Brazilian primary healthcare setting - Ana Paula Tussi Leite; Géssica Luana Antunes; Amanda Paz Santos; Ingrid Rodrigues Fernandes; Lauren Sezerá Costa; Tássia Rolim Camargo; Camila Bonalume Dall’ Aqua; Fernando Rovedder Boita; Alessandra da Silva Mota; Mariana Motta Dias da Silva; Mariah Prata Soldi Passos Taube; Bruna Silveira da Rosa; et al. (Trials)
Abstract Background Asthma is one of the most prevalent chronic pulmonary diseases, affecting approximately 20 million Brazilian people. Most patients with asthma in Brazil present with uncontrolled disease, leading to high morbidity and mortality rates. Therefore, an effective educational intervention focused on asthma management in primary health care (PHC) is expected to reduce hospitalization rates, emergency visits, and direct public health costs, improving the quality of life of patients. Methods The CuidAR study is a controlled and randomized superiority trial conducted at cluster level, with two arms and a 1:1 allocation ratio. A total of 40 PHC centers will be selected, covering all macro-regions of Brazil. Twenty centers will be randomized to the intervention group (healthcare professional teams will undertake an asthma management program) and the other 20 centers will be randomized to the control group (current standard of care). This study aims to enroll 960 participants aged 6 to 65, all of whom have a physician-diagnosed case of uncontrolled asthma and meet the eligibility criteria. The primary outcome is the asthma-related hospitalization rate. Data collected will be analyzed after all participants have completed a 12-month follow-up period. Discussion Empowering the multidisciplinary healthcare team on asthma management at a national level in the PHC centers, while addressing the substantial burden of asthma in Brazil, holds the potential to reduce asthma hospitalization rates in alignment with global health priorities, ultimately reducing direct public health costs. Trial registration Brazilian Registry of Clinical Trials (ReBEC) RBR-9xtq9p6. Registered on January 16, 2023, https://ensaiosclinicos.gov.br/rg/RBR-9xtq9p6 .